SOFAT as a Putative Marker of Osteoclasts in Bone Lesions. Issue 6 (July 2019) - Cândido-Soares, Lara E.; Martinez, Elizabeth F.; de Araújo, Vera C.; Araújo, Ney S.; Freitas, Nadir S.; Napimoga, Marcelo H.
Abstract : Secreted osteoclastogenic factor of activated T cells (SOFAT) is a novel activated human T-cell–secreted cytokine that induce osteoclastogenesis in a RANKL-independent manner. The aim of this study was to evaluate the immunohistochemical expression of SOFAT in intraosseous and extraosseous lesions. Thirty-two oral biopsies were divided into 2 groups: (1) intraosseous lesions—4 cases of cherubism, 5 central giant cell lesions, 3 osteoblastomas, 3 cementoblastomas, 2 periapical lesions and (2) extraosseous lesions—5 peripheral giant cell lesions, 5 cases of oral paracoccidioidomycosis, and 5 foreign body reactions. Immunohistochemistry was performed for SOFAT and tartrate-resistant acid phosphatase. Image analysis consisted of a descriptive evaluation of the immunohistochemical staining pattern observed. Tartrate-resistant acid phosphatase-positive lesions included those containing multinucleated giant cells (MGC) from both groups. SOFAT was positive in MGC of the intraosseous lesions group, except in periapical foreign body reactions as well as extraosseous lesions. SOFAT was shown to be a putative marker of osteoclasts, which proved useful to differentiate them from multinucleated macrophages. Osteoclast induction may be both dependent and independent from the RANK/RANKL/OPG pathway and independent from the bone microenvironment. Abstract : Supplemental Digital Content is available in the text.